Health information seeking behaviour: the librarian's role in supporting digital and health literacy. (20th September 2019) - Butler, Rachel
Abstract: This paper is based on Rachel Butler's dissertation carried out at the University of Sheffield as part of the MA Library and Information Services Management. The study examines people's online health information seeking skills, with the specific aim to identify how libraries and health services can work together in supporting digital and health literacy. A survey approach is used to explore online searching habits as well as librarian and health professionals' views on health literacy. The key findings indicate that whilst the majority of respondents consider themselves to be health literate, there was an overall agreement that effective education and support could be achieved through the collaboration between libraries and health services, and specifically to signpost information and to provide targeted education. The limitations of the research for dissertation are recognised leading to recommendations that further study focuses on the impact of signposting and education on health literacy.F.J.